Geriatric surgery is about disease, not age - Preston, Stephen D (The Royal Society of Medicine, 2008)
Maintaining life span and quality of life remains a valid aim of surgery in elderly people. Surgery can be an effective way of restoring both length and quality of life to older people. Minimally invasive techniques and surgery under local anaesthesia make fewer demands on geriatric physiology; given that co-morbidity is a stronger predictor of outcome from surgery than age, this is a significant consideration.